(untitled) (Bangladesh Journal of Animal Science, 2016)
An experiment was conducted with 60 day old Cobb-500 broiler chicks for a period of 28 days with the aims of investigating the effects of different level of garlic powder on growth performance, carcass characteristics and meat quality of broilers to produce safe broiler meat. The experimental broiler chicks were divided randomly into four different groups with three replications having 5 chicks in each. Maize-soybean based diet was used as basal diet for group 1. Basal diet was supplemented with 1%, 2% and 3% garlic powder on fresh basis for group 2, 3, and 4 respectively. The broiler of groups 2, 3, and 4 were showed significantly (p>0.05) higher body weight than control group at 4 weeks of age. Feed conversion ratio of group 2, 3, and 4 were significantly (p>0.05) lower than group 1. Group 2 was given significantly lower fat percentage than other groups. Group 3 and 4 showed more or less similar fat content but lower than control groups. Thus, it may be concluded that garlic powder may be used in chicken diet. Bang. J. Anim. Sci. 2016. 45 (2): 79-83